Key factors around ocean-based power in the Caribbean region, via Trinidad and Tobago. (October 2015) - Henry, Legena; Bridge, Jacqueline; Henderson, Mark; Keleher, Kevin; Barry, Megan; Goodwin, Geoff; Namugayi, Deborah; Morris, Marisha; Oaks, Benjamin; Dalrymple, Odesma; Shrake, Scott; Ota, Akane; et al.
Abstract: Caribbean residents outside of Trinidad and Tobago primarily utilize hydrocarbons for electricity, earning them the highest energy bills in the world. Apart from global climate change concerns, these high energy prices make it clear that alternative energy must be sourced for the Caribbean region. With Trinidad and Tobago׳s large offshore hydrocarbon reserves, Trinidad and Tobago has bolstered its economy and its expertise in offshore engineering and technology in the past five decades. Caribbean regional efforts to find ocean-based renewable energy resources can largely exploit the aforementioned advantages and opportunities in Trinidad and Tobago. The present work involves a collaboration between a team of engineers to collect and analyze oceanic data in Trinidad and Tobago, and a team of sustainability scholars to survey the maritime context of Trinidad and Tobago via the lens of sustainable development. This is done to appropriately contextualize Trinidad and Tobago, which is the territory via which Caribbean regional ocean-based power exploration is recommended.